Zniekształcenia strukturalne osobowości badacza jako przyczyna błędów diagnostycznych - Jagieła, Jarosław (Edukacyjna Analiza Transakcyjna, 2013)
The article explores structural distortions of the researcher’s personality (contaminations and exclusions) as one of the causes of his/her diagnostic mistakes. Integrated personality of a diagnos- tician is an important factor which can prevent making mistakes. Such personality allows for the verification of one’s judgements and hypotheses, offers the possibility to revise one’s achieve- ments, and successfully deal with stereotypes or superstitions. The author postulates incorporating development and formation of desirable personality traits in diagnosticians’ vocational training.